Divergence of the Floral A-Function between an Asterid and a Rosid Species. Issue 7 (23rd June 2017) - Morel, Patrice; Heijmans, Klaas; Rozier, Frédérique; Zethof, Jan; Chamot, Sophy; Bento, Suzanne Rodrigues; Vialette-Guiraud, Aurélie; Chambrier, Pierre; Trehin, Christophe; Vandenbussche, Michiel
Abstract : Petunia research suggests that the mechanisms controlling the spatial restriction of floral organ identity genes are more diverse than the well-conserved B and C floral organ identity functions. Abstract: The ABC model is widely used as a genetic framework for understanding floral development and evolution. In this model, the A-function is required for the development of sepals and petals and to antagonize the C-function in the outer floral whorls. In the rosid species Arabidopsis thaliana, the AP2-type AP2 transcription factor represents a major A-function protein, but how the A-function is encoded in other species is not well understood. Here, we show that in the asterid species petunia ( Petunia hybrida ), AP2B/BLIND ENHANCER ( BEN ) confines the C-function to the inner petunia floral whorls, in parallel with the microRNA BLIND . BEN belongs to the TOE-type AP2 gene family, members of which control flowering time in Arabidopsis. In turn, we demonstrate that the petunia AP2-type REPRESSOR OF B-FUNCTION ( ROB ) genes repress the B-function (but not the C-function) in the first floral whorl, together with BEN . We propose a combinatorial model for patterning the B- and C-functions, leading to the homeotic conversion of sepals into petals, carpels, or stamens, depending on the genetic context. Combined with earlier results, our findings suggest that the molecular mechanisms controlling the spatial restriction of the floral organ identity genes are more diverse than the well-conserved B and C floral organ identity functions.